Naturalna stopa procentowa a reguła Taylora - Hetmańczuk, Adam; Natalii, Marek; Sucholiński, Andrzej (Natural rate of interest and the Taylor rule, 2006)
The subject of this paper is interest rate setting by the monetary authority. The first part of this article presents the influence of the Natural Rate of Interest (NRI) on inflation stabilization via nominal interest rates of the Central Bank. The basic idea of NRI was originally formulated by Knut Wicksell. The new definitions of Natural Rate of Interest, considering inflation, were given by T. Laubach, J. C. Williams and A.S. Blinder. In the second part of this article the authors present the Taylor rule as an interest-rate feedback rule of the following form: an interest rate of the Central Bank is a linear function of the deviation of inflation from its target and the deviation of real GDP from its potential plus current inflation rate and real interest rate in the equilibrium. The Taylor rule seeks to stabilize inflation around the middle-run target. The authors want to answer the question: How useful are the Natural Rate of Interest and the Taylor Rule as an interest rate rule for inflation targeting monetary strategy. The discussion suggests that the combination of NRI and the Taylor rule may be successful for practical monetary policy making: to stabilize the inflation rate in the long run and the purchasing power of money
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1131, s. 198-216